Hak dan Kewajiban Warga Negara dalam Konstitusi Amerika Serikat - Sembiring, Marliana Br.; Hasibuan, Khotimatul Mar’ah; Nafis, Badratun (Jurnal Pengetahuan Sosial dan Sejarah, 2025)
This study aims to examine the regulation of citizens' rights and obligations as stipulated in the United States Constitution, especially in the Bill of Rights, and to analyze the relevance of its implementation for the development of the legal system in Indonesia. Using qualitative methods and a descriptive approach, this study uses various academic sources, including books, journals, and official documents. The results of the study indicate that the fundamental rights of United States citizens, such as freedom of religion, speech, and legal protection, are protected through amendments to the Bill of Rights, while obligations such as paying taxes, obeying the law, and participating in the justice system are intended to maintain a balance between individual freedom and social responsibility. In addition, this study also highlights the importance of a transparent and fair justice system in protecting citizens' rights from violations. The main value of this study lies in its ability to provide insight into the development of a legal system in Indonesia that emphasizes a balance between citizens' rights and obligations. By studying the implementation of the principles of democracy and social justice in the United States, this study contributes to the development of just and sustainable legal governance.